Nucleotide sequences of mitochondrial cytochrome b gene for phylogeny of some species of Rodentia (Bioscience Journal, 2023)
Order Rodentia contains approximately half of all living mammalian species. Most of the living species diversity within rodents is within five monophyletic radiations: Hystricognathi, Sciuridae, Geomyoidea, Dipodidae, and Muroidea. The samples collected across different areas of Egypt were analyzed by means of mitochondrial cytochrome b gene sequence analysis to ascertain the true taxonomic status between the studied species. For phylogenetic analysis, the cytochrome b sequences from this study were combined with previously published data. This study reveals that all species were divided into two main clades, the first for the Gerbillinae taxon and the second for the other studied genera in the molecular phylogenetic trees and demonstrates that Gerbillus species form a sister group with Dipodillus species. The phylogenetic relationships specified for the murine genera. Clustering was obtained between Mus and Rattus as well as in all Gerbillinae species. This study provides the first insight into the genetic diversity of some rodents in Egypt.